Modelo de sustitución de importaciones: Efectos financieros en la industria siderúrgica de Boyacá. caso Acerías Paz Del Rio. - Pineda Abril, Mayerly Alexandra (Universidad Antonio Nariño, 2021)
The purpose of this document is to analyze the implementation of the import substitution model in the steel sector in Boyacá, taking the Acerías Paz del Río SA company as a reference. Methodologically, secondary information is required, with historical documents on the evolution of the steel activity. in Colombia, and financial data of the company, since the beginning of its operation. From the analysis it is established that the model was accompanied by a policy of protection of the national industry, with a positive effect at the beginning, which was not accompanied by a process of technological reconversion, so that, given a change in the development scheme, it conditioned the financial viability of various productive activities, including the steel industry.